2017
DOI: 10.1017/s0030605317000862
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to illegal behaviour and conservation in western Tanzania

Abstract: Natural resources in and around protected areas in many countries in Africa are under intense pressure as a result of illegal behaviour, such as fishing, hunting and logging. A better understanding of local people's perceptions of the nature of illegal behaviour and the relevance of conservation actions would be useful in informing conservation decisions. We gathered information on the attitudes and perceptions of communities in the vicinity of Ugalla Game Reserve in western Tanzania regarding illegal behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Obstacles were also recorded, such as patrol vehicle breakdowns and getting stuck. We categorised signs into four common illegal activity types in Ugalla (e.g., Wilfred et al, ), namely logging, poaching, fishing and unauthorised entry (signs that indicated the presence of unauthorised individuals in the reserve, but could not be directly associated with other illegal activities). Waypoints were recorded every 20–30 min as patrols moved along Ugalla roads, and were later downloaded from GPS units to the SMART database.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obstacles were also recorded, such as patrol vehicle breakdowns and getting stuck. We categorised signs into four common illegal activity types in Ugalla (e.g., Wilfred et al, ), namely logging, poaching, fishing and unauthorised entry (signs that indicated the presence of unauthorised individuals in the reserve, but could not be directly associated with other illegal activities). Waypoints were recorded every 20–30 min as patrols moved along Ugalla roads, and were later downloaded from GPS units to the SMART database.…”
Section: Methodsmentioning
confidence: 99%
“…Ugalla Game Reserve (hereafter Ugalla), in western Tanzania, experiences high levels of illegal activity (Wilfred, Milner‐Gulland, & Travers, ). Logging and the killing of elephants ( Loxodonta africana , [Anonymous, 1827]) and other species of conservation importance are widespread in the area (Wilfred & MacColl, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where trophy hunting provides few or no benefits to local communities, the practice fails to alleviate neocolonial conditions of poverty, corruption, and exploitation (e.g., Benjaminsen & Svarstad 2010; Wilfred et al. 2019). Meanwhile, Western opposition to trophy hunting is dismissed as antiscientific and emotional (Macdonald et al.…”
Section: Moral Residue In Conservationmentioning
confidence: 99%
“…Omali' programme logic model, demonstrating the conceptualised pathway for the expected impact of the campaign activities on sea turtle populations Consumption of sea turtle eggs and meat was measured using the unmatched count technique (UCT). This has been widely used in social science to uncover the prevalence of a diverse range of sensitive and/or illegal behaviours, including logging (Wilfred et al, 2019), bushmeat poaching (Nuno et al, 2013) and dangerous driving (Sheppard & Earleywine, 2013). Survey respondents are randomly allocated into two groups: control and treatment (Hinsley et al, 2019).…”
Section: F I G U R E 1 'Tataluga -Mém Dimentioning
confidence: 99%